Natural remedies in burn care: a systematic review and network meta-analysis - Ismail, Muhammad Azri; Tanjaya, Krisanto; Wruhastanti, Gisella Sekar; Siswanto, Yudi (Medical Journal of Indonesia, 2024)
BACKGROUND Burn injuries are a global public health issue that impact healing time and cause complications. While silver sulfadiazine (SSD) cream is commonly used for treatment, research indicates that SSD can hinder the wound healing process. Natural alternatives like Aloe vera, honey, and amniotic membranes have shown promise in promoting wound healing. This study aimed to evaluate their efficacy by their wound healing time and infection rate. METHODS 3 independent reviewers conducted a literature search across 6 databases (Cochrane Central Register of Controlled Trials, PubMed, ScienceDirect, Taylor & Francis, Wiley, and ProQuest). Quality assessment was conducted using the Cochrane Risk of Bias 2 tool, while network meta-analysis was performed using the netmeta package in R. The variable in this study is the average time to burn wound healing and infection occurrence by analyzing MD data or OR of each intervention, with 95% CI to calculate the efficacy. RESULTS A total of 3,434 patients from 37 studies were included. In the analysis of 26 studies comparing the healing time to SSD, A. vera has the best efficacy (MD: −4.75; 95% CI: −8.67 to −0.86), followed by amniotic membrane (MD: −4.71; 95% CI: −7.45 to −1.97), and honey (MD: −4.25; 95% CI: −6.76 to −1.73). Meanwhile, the occurrence of infection analysis in burn wounds across 24 studies highlighted that honey has the lowest infection rate (OR: 0.09; 95% CI: 0.04 to 0.23) and was the only statistically significant finding when compared to SSD. CONCLUSIONS Aloe vera and amniotic membrane are effective for wound healing, while honey is particularly effective in preventing wound infection in patients with burn injuries.